"I call him father of us all": vicarious transcendence at the B. B. King Museum and Delta Interpretive Center*. Issue 1 (2nd January 2018) - Gatchet, Roger Davis; King, Stephen A.
ABSTRACT: This essay advocates closer attention to the relationship between transcendent rhetoric and public memory sites. Through an analysis of the B. B. King Museum and Delta Interpretive Center in Indianola, Mississippi, the essay introduces the concept of vicarious transcendence, a powerful, yet underexplored mode of public discourse that highlights how visitors arrive at a transcendent state via the transcendent journey of another agent. As the state's premier destination for blues tourists, the King Museum also becomes a vehicle for Mississippi's vicarious transcendence of its own legacy of slavery and systemic racism.